An automated LS(β)- NaI(Tl)(γ) coincidence system as absolute standard for radioactivity measurements. (July 2018) - Joseph, Leena; Das, A.P.; Ravindra, Anuradha; Kulkarni, D.B.; Kulkarni, M.S.
Abstract: 4πβ-γ coincidence method is a powerful and widely used method to determine the absolute activity concentration of radioactive solutions. A new automated liquid scintillator based coincidence system has been designed, developed, tested and established as absolute standard for radioactivity measurements. The automation is achieved using PLC (programmable logic controller) and SCADA (supervisory control and data acquisition). Radioactive solution of 60 Co was standardized to compare the performance of the automated system with proportional counter based absolute standard maintained in the laboratory. The activity concentrations determined using these two systems were in very good agreement; the new automated system can be used for absolute measurement of activity concentration of radioactive solutions. Highlights: A new automated liquid scintillator based coincidence system has been designed, developed, tested. The automation is achieved using PLC (programmable logic controller) and SCADA (supervisory control and data acquisition). Radioactive solution of 60 Co was standardized to compare performance with proportional counter based primary standard. The results of activity concentration obtained using two systems are comparable within uncertainty limits.